2005
DOI: 10.1097/01.prs.0000156153.17258.ce
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Thigh Flap Reconstruction of Large External Facial Skin Defects: A Follow-Up Study on Functional and Aesthetic Recipient- and Donor-Site Outcome

Abstract: Careful patient selection may further improve aesthetic outcome of the anterolateral thigh flap. The versatility in design and composition of the anterolateral thigh flap and the low donor-site morbidity and satisfactory recipient-site outcome make it a valuable option in reconstruction of external skin defects in the head and neck region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 30 publications
3
46
1
1
Order By: Relevance
“…12 Large, deep, complex or compromised wounds often have to be reconstructed with distant or free flaps but they usually lead to poor colour and texture match for facial skin. 17 Primary reconstruction of such defects with microsurgical techniques is now the protocol. Although free microvascular tissue transfer may be an acceptable solution, especially in multilayer defects, differences of skin colour and structure of the harvested tissue may make them conspicuous.…”
Section: Discussionmentioning
confidence: 99%
“…12 Large, deep, complex or compromised wounds often have to be reconstructed with distant or free flaps but they usually lead to poor colour and texture match for facial skin. 17 Primary reconstruction of such defects with microsurgical techniques is now the protocol. Although free microvascular tissue transfer may be an acceptable solution, especially in multilayer defects, differences of skin colour and structure of the harvested tissue may make them conspicuous.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, such as Malata et al 21 and Amin et al, 22 reported their experience with ALT flap for skull base and craniofacial defects reconstruction, focusing on the large amount of well revascularized tissue provided used for the filling of the death spaces, the low rate of complications and the stability of the results obtained. Finally, Mureau et al 23 and Hong et al 24 presented their experience with the use of ALT flap for the external coverage reconstruction, with particular care to the donor site morbidity and the final cosmetic outcome.…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of the patients who were content with the aesthetic results of the operation was comparable to the results previously published studies using the same tool. [13] The absence of a control group is a limitation for the study as well as the few numbers of cases. Strength of the study is that it was done in one centre with a tight control of the protocol including the surgical team and technique and outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] − We modified the flap characteristics to be evaluated according to our expert's opinion. Our evaluation sheet included the following flap characteristics:…”
Section: Aesthetic Outcome Assessmentmentioning
confidence: 99%